Opsin Evolution in Flower-Visiting Beetles - Sharkey, Camilla R.; Powell, Gareth S.; Bybee, Seth M. (Frontiers in Ecology and Evolution, 2021)
Flowers have evolved signals that exploit the sensory systems of insect visitors. In the case of visual cues, color signals are thought to have been shaped in large part by the spectral sensitivity of key pollinators, such as hymenopterans. Beetles were some of the first plant pollinators, pre-dating the angiosperm radiation but with the exception of a few well-studied species, the evolution of flower-visiting beetle visual systems is poorly understood. Thus, the ability of beetles to detect and distinguish flower color signals and perhaps their potential role in shaping flower coloration is not well understood. Traditional models of pollinator visual systems often assume a putative tri- or tetrachromatic flower-visitor, as is found in bees, flies and butterflies. Beetles are unique among modern pollinators as ancestrally they did not possess the machinery for trichromatic vision, lacking the blue-sensitive photoreceptor class. Research on the evolution of visual genes responsible for wavelength sensitivity (opsins) has revealed that beetles with putative tri- and tetrachromatic visual systems have evolved independently, along multiple lineages. We explore the evolution of beetle visual genes using newly generated and publicly available RNA-seq data from 25 species with flower associations, including previously unexplored key flower-visitor groups and 20 non-flower visiting relatives. Our findings serve as a resource to inform and guide future studies on beetle-flower interactions, where insight from both signal and receiver is needed to better understand these poorly explored systems.